Quadrature demodulation in line‐scan focal modulation microscopy for imaging three‐dimensional zebrafish neural structure. Issue 1 (16th October 2019) - Shen, Shuhao; Wu, Jian; Chen, Nanguang
Abstract: Visualizing biological processes in neuroscience requires in vivo functional imaging at single‐neuron resolution, high image acquisition speed and strong optical sectioning ability. However, due to light scattering of in tissue, very often conventional wide‐field fluorescence microscopes are unable to resolve cells in the presence of a strong out‐of‐focus background. Line‐scan focal modulation microscopy enables high temporal resolution and good optical sectioning ability at the same time. Here we demonstrate a quadrature demodulation method to extract the focal information with an extended frequency bandwidth and therefore higher spatial resolution. The performance of the demodulation scheme in line‐scan focal modulation microscope has been evaluated by performing imaging experiments with fluorescence beads and zebrafish neural structure. Reduced background, reduced artifacts and more detailed morphological information are evident in the obtained images. Abstract : Line‐scan focal modulation microscopy enables high speed acquisition and good optical sectioning ability at the same time. To further improve the image quality, this article presents a quadrature demodulation method to extract the focal information with an extended frequency bandwidth and therefore higher spatial resolution. Reduced background, reduced artifacts and more detailed morphological information can be retrieved in the three‐dimensional zebrafish neural images, contributing to the neuroscience research.